ANALISIS PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN PERTAMBANGAN DI BEI TAHUN 2010-2014 - Farianita Lestari; Dewi Rahmayanti (Unib Press Universitas Bengkulu, 2017)
The purpose of this research to analyze the influence of Return On Asset (ROA) and Net Profit Margin (NPM) on corporate value with CSR as a moderating variable in the mining company listed on the Indonesia Stock Exchange in the period of 2010 -2014. The number of population for this research is 40 company and the number of sample that examined after passed the purposive sampling phase is 11 company. The analysis method used in this research that is with moderated regression analysis, panel data regression, hypothesis test that is determinant coefficient, test F, and test T. From the result of simultan analysis variable Return On Asset (ROA), Net Profit Margin (NPM) and Corporate Social Responsibility (CSR) have significant influence toward corporate value (tobin’s Q). The result of partial this research shows that only Return On Asset (ROA) have significant influence toward corporate value (tobin’s Q). The disclosure of Corporate Social Responsibility (CSR) is can’t able to moderate relation of NPM and corporate value, and able to moderate relation of ROA and corporate value